Cardiovascular Characteristics and Outcomes of Young Patients with COVID-19 - Antonin Trimaille; Sophie Ribeyrolles; Charles Fauvel; Corentin Chaumont; Orianne Weizman; Thibaut Pommier; Joffrey Cellier; Laura Geneste; Vassili Panagides; Wassima Marsou; Antoine Deney; Sabir Attou; et al. (Journal of Cardiovascular Development and Disease, 2021)
Although 18–45-year-old (y-o) patients represent a significant proportion of patients hospitalized for COVID-19, data concerning the young population remain scarce. The Critical COVID France (CCF) study was an observational study including consecutive patients hospitalized for COVID-19 in 24 centers between 26 February and 20 April 2020. The primary composite outcome included transfer to the intensive care unit (ICU) or in-hospital death. Secondary outcomes were cardiovascular (CV) complications. Among 2868 patients, 321 (11.2%) patients were in the 18–45-y-o range. In comparison with older patients, young patients were more likely to have class 2 obesity and less likely to have hypertension, diabetes and dyslipidemia. The primary outcome occurred less frequently in 18–45-y-o patients in comparison with patients > 45 years old (y/o) (16.8% vs. 30.7%, p < 0.001). The 18–45-y-o patients presented with pericarditis (2.2% vs. 0.5%, p = 0.003) and myocarditis (2.5% vs. 0.6%, p = 0.002) more frequently than patients >45 y/o. Acute heart failure occurred less frequently in 18–45-y-o patients (0.9% vs. 7.2%, p < 0.001), while thrombotic complications were similar in young and older patients. Whereas both transfer to the ICU and in-hospital death occurred less frequently in young patients, COVID-19 seemed to have a particular CV impact in this population.